Analysis of Ethical and Legal Aspects in Implementing a Medical Record System in Hospitals on Patient Health Practices - Irsyam Risdawati (Yayasan Multidimensi Kreatif, 2024)
Implementing a medical record system in a hospital plays an integral role in managing patient health information. This article analyzes the ethical and legal aspects involving medical record management, and their impact on patient health practices in hospitals. Findings regarding breaches of confidentiality, inaccurate information, inappropriate access, delays in patient access, and non-transparency of information are the main focus. Ethical implications involve the risk of losing patient trust and the establishment of a positive doctor-patient relationship, while legal implications include potential lawsuits by patients and administrative sanctions against medical record system administrators. Thus, improvements in regulatory compliance, increased ethical awareness among health workers, and implementation of best practices are recognized as crucial steps in maintaining the integrity of the health system and ensuring ethical and legally compliant health practices. In conclusion, collaboration between stakeholders and a holistic approach are needed to achieve the implementation of a medical record system that prioritizes patient rights and interests, strengthens trust, and improves the quality of health services in hospitals.